Endobronchial Electrocautery and Argon Plasma Coagulation: A Practical Approach - Alain Tremblay; Charles-Hugo Marquette (Canadian Respiratory Journal)
The present review covers the technical and practical aspects of endobronchial electrocautery, including argon plasma coagulation, which have great potential for widespread use by pulmonologists around the world. The various electrocautery modes, power settings and electrode probes are described in detail, and the authors' clinical and technical approach is demonstrated with a narrative description and brief case presentations. Malignant airway obstruction, hemoptysis, web-like stenosis, stent related granulation tissue and early lung carcinomas are the most common indications for treatment. Advantages of electrocautery, such as low cost, rapid effect, safety and ease of use, are contrasted to other endobronchial therapeutic modalities. Published experience with electrocautery is reviewed.